On the Validity of the “Thin” and “Thick” Double-Layer Assumptions When Calculating Streaming Currents in Porous Media - Matthew D. Jackson; Eli Leinov (International Journal of Geophysics)
We find that the thin double layer assumption, in which the thickness of the electrical diffuse layer is assumed small compared to the radius of curvature of a pore or throat, is valid in a capillary tubes model so long as the capillary radius is >200 times the double layer thickness, while the thick double layer assumption, in which the diffuse layer is assumed to extend across the entire pore or throat, is valid so long as the capillary radius is >6 times smaller than the double layer thickness. At low surface charge density (<10 mC⋅m−2) or high electrolyte concentration (>0.5 M) the validity criteria are less stringent. Our results suggest that the thin double layer assumption is valid in sandstones at low specific surface charge (<10 mC⋅m−2), but may not be valid in sandstones of moderate- to small pore-throat size at higher surface charge if the brine concentration is low (<0.001 M). The thick double layer assumption is likely to be valid in mudstones at low brine concentration (<0.1 M) and surface charge (<10 mC⋅m−2), but at higher surface charge, it is likely to be valid only at low brine concentration (<0.003 M). Consequently, neither assumption may be valid in mudstones saturated with natural brines.